Pendampingan NIB dan Sertifikasi Halal sebagai Upaya Mendorong Legalitas UMKM di Rewwin, Waru, Sidoarjo - Atina Nabila Ahmad (Lembaga Pengembangan Kinerja Dosen, 2026)
Assistance in obtaining a Business License Number (NIB) and halal certification at Rewwin Housing was carried out as a strategic effort to promote legality and increase the competitiveness of MSMEs. In general, many business actors still do not have legal status due to limited knowledge regarding administrative procedures and digital licensing systems. In fact, business legality is a crucial aspect that can increase consumer trust, expand market access, and strengthen a business's position amidst competition. Sobar et al. (2023),